Fraternal capital : peasant-workers, self-made men, and globalization in provincial India - Chari, Sharad (Stanford University Press, 2004)
"Fraternal Capital examines class, gender, and work in Tiruppur, South India, where export of knitted garments has been led by a networked fraternity of owners of working-class and Gounder caste origins, who explain their class mobility as hinging on their "toil." This book asks how these self-made men drew from their agrarian past to turn Gounder toil into capital, and how they continue to make an entire town work for the global economy."--BOOK JACKET.